lncRNA-ATB functions as a competing endogenous RNA to promote YAP1 by sponging miR-590-5p in malignant melanoma - Mou, Kuanhou (Int J Oncol, 2018)
The critical long non-coding RNAs (lncRNAs) involved in the carcinogenesis and progression of malignant melanoma (MM) have not been fully investigated. In the present study, it was identified that lncRNA activated by transforming growth factor-β (lncRNA-ATB) was upregulated in MM tissues and cells compared with benign nevus cells and human melanocytes, via comparative lncRNA screening from Gene Expression Omnibus datasets and reverse transcription-quantitative polymerase chain reaction analysis. Furthermore, lncRNA-ATB promoted the cell proliferation, cell migration, and cell invasion of MM cells in vitro, and tumor growth in vivo. It was additionally identified that lncRNA-ATB attenuated cell cycle arrest and inhibited cellular apoptosis in MM cells. Finally, it was demonstrated that lncRNA-ATB functions as a competing endogenous RNA (ceRNA) to enhance Yes associated protein 1 expression by competitively sponging microRNA miR-590-5p in MM cells. In conclusion, the present study revealed the expression and roles of lncRNA-ATB in MM, and indicated that lncRNA-ATB functions as a ceRNA to promote MM proliferation and invasion by sponging miR-590-5p.